(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the development trends of small businesses and entrepreneurs in the context of a green economy using the example of the Namangan region. The issues of environmentally sustainable production, the introduction of energy-saving technologies, the use of renewable energy sources, and the rational use of resources in the region are studied. According to the results of the study, the application of green economy principles to small business activities helps to increase the competitiveness of enterprises, reduce costs, and create new jobs. Also, proposals have been developed on the prospects for the development of green entrepreneurship in the Namangan region and existing problems.